The Journey of Arsenic from Soil to Grain in Rice - Awasthi, Surabhi; Chauhan, Reshu; Srivastava, Sudhakar; Tripathi, Rudra D. (Frontiers in Plant Science, 2017)
Arsenic (As) is a non-essential toxic metalloid whose elevated concentration in rice grains is a serious issue both for rice yield and quality, and for human health. The rice-As interactions, hence, have been studied extensively in past few decades. A deep understanding of factors influencing As uptake and transport from soil to grains can be helpful to tackle this issue so as to minimize grain As levels. Arsenic uptake at the root surface by rice plants depends on factors like iron plaque and radial oxygen loss. There is involvement of a number of transporters viz., phosphate transporters and aquaglyceroporins in the uptake and transport of different As species and in the movement to subcellular compartments. These processes are also affected by sulfur availability and consequently on the level of thiol (-SH)-containing As binding peptides viz., glutathione (GSH) and phytochelatins (PCs). Further, the role of phloem in As movement to the grains is also suggested. This review presents a detailed map of journey of As from soil to the grains. The implications for the utilization of available knowledge in minimizing As in rice grains are presented.